Remittances to Latin America from migrants in the United States: assessing the impact of amnesty programs - Catalina Amuedo-Dorantes; Francesca Mazzolari (Institute for the Study of Labor (IZA), 2009)
The magnitude of remittance flows to Latin America exceeds the combined inflows of foreign direct investment and official development assistance to the region. Since the United States is the destination country of the vast majority of migrants from Mexico, as well as from other Latin American countries, U.S. immigration policy can have a significant impact on the volume of remittances to the Latin American region. This paper studies how a generalized amnesty - a provision in the 1986 Immigration Reform and Control Act (IRCA), affected immigrants' remitting patterns. In models that control for immigrants' length of residence in the United States and for economic conditions in both the U.S. state of residence and the country of origin, we estimate substantial post-legalization drops in remittances sent home by Mexican-born migrants who legalized through IRCA. Given the potential positive impact of remittances on investment levels, entrepreneurship rates and the development of the financial sector, this finding underscores the importance of gaining a better understanding of the impact that immigration policies in immigrant-receiving countries may have on the stream of remittance flows to immigrant-sending communities in developing regions.
urn:nbn:de:101:1-20090825575
Keywords: F24; O15; 330; Remittances; Latin American migrants; legal status; amnesty; Rücküberweisung (Migranten); Illegale Einwanderung; Straffreiheit; Einwanderungsrecht; Mexikaner; USA; Mexiko